Learning to improvise in jazz music for a modern music student through copying other musicians technique / Izham Reduzan - Reduzan, Izham (Faculty of Music, 2017)
Researcher chose this topic is to identify whether by copying other musicians improvisation technique can improve modern music student in UiTM to improvise in jazz music. Jazz improvisation is an important aspect of jazz. According to Marsalis (2007), In Jazz improvisation isn't a matter of just making any 01‘ thing up. Jazz, like any language, has its own grammar and vocabulary. There's no right or wrong, just some choices that are better than others. It involves many aspects in terms of music theory and it also has to be coupled with the ability and efficiency of a musician to think sensibly to enable it to react better in this music